Detection of Cellular Senescence in Human Primary Melanocytes and Malignant Melanoma Cells In Vitro - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (Cells, 2022)
Detection and quantification of senescent cells remain difficult due to variable phenotypes and the absence of highly specific and reliable biomarkers. It is therefore widely accepted to use a combination of multiple markers and cellular characteristics to define senescent cells in vitro. The exact choice of these markers is a subject of ongoing discussion and usually depends on objective reasons such as cell type and treatment conditions, as well as subjective considerations including feasibility and personal experience. This study aims to provide a comprehensive comparison of biomarkers and cellular characteristics used to detect senescence in melanocytic systems. Each marker was assessed in primary human melanocytes that overexpress mutant BRAFV600E, as it is commonly found in melanocytic nevi, and melanoma cells after treatment with the chemotherapeutic agent etoposide. The combined use of these two experimental settings is thought to allow profound conclusions on the choice of senescence biomarkers when working with melanocytic systems. Further, this study supports the development of standardized senescence detection and quantification by providing a comparative analysis that might also be helpful for other cell types and experimental conditions.
CRIS-Team Scopus Importer:2022-05-13
Keywords: beta-galactosidase; melanocyte; melanoma; senescence